Sociophonetics - Kendall, Tyler, 1976-; Fridland, Valerie (Cambridge : Cambridge University Press, 2021)
Sociophonetics focuses on the relationship between phonetic or phonological form on the one hand, and social and regional factors on the other, working across fields as diverse as sociolinguistics, phonetics, speech sciences and psycholinguistics. Covering methodological, theoretical and computational approaches, this engaging introduction to sociophonetics brings new insights to age-old questions about language variation and change, and to the broader nature of language. It includes examples of important work on speech perception, focusing on vowels and sibilants throughout to provide detailed exemplification. The accompanying website provides a range of online resources, including audio files, data processing scripts and links. Written in an accessible style, this book will be welcomed by students and researchers in sociolinguistics, phonetics, speech sciences and psycholinguistics.
Title from publisher's bibliographic system (viewed on 26 Feb 2021).
Keywords: Sociophonetics; Sociolinguistics; Grammar, Comparative and general -- Phonology